From Anatomical Modifications to Skin Quality: Case Series of Botulinum Toxin and Facial Fillers for Facial Feminization in Transgender Women - Viscomi B (Dove Medical Press, 2022)
Bianca Viscomi Dermatology, Private Practice, São Paulo, São Paulo, BrazilCorrespondence: Bianca Viscomi, Dermatology, Private Practice, R Correia Dias, 530 suite 131, São Paulo, São Paulo, ZIP 04104-001, Brazil, Tel +55 11 97222-0525 ; +55 113051-2304, Email biancaviscomi@yahoo.com.brAbstract: A transgender individual is someone who does not identify with his or her biological sex1. During the transgender transition process, minimally invasive procedures (MIP) provide a versatile tool in the clinician’s therapeutic armamentarium, since the changes can be impactful for the patient, yet reversible, especially for the patient who is unsure about proceeding with a definite surgery. We report 5 cases of facial feminization of transgender women, illustrating the use of minimally invasive facial remodeling procedures for male-to-female transitioning patients.Keywords: transgender, feminization, botulinum toxin, hyaluronic acid fillers, calcium hydroxyapatite, skin quality